Pengaruh Kemandirian, Efektivitas Pendapatan Asli Daerah dan Belanja Daerah terhadap Kinerja Keuangan Kabupaten/Kota di Aceh - Mayanti, Farista; Rizky, Fitrian; Ariansyah, Ricky (Aceh Cooperative Care, 2023)
The aim of this study was to determine whether regional autonomy, the effectiveness of regional income, and regional expenditure affect financial performance. Using the census method for sampling, there are 23 districts/cities sampled in this study, namely regency/cities in Aceh in 2018-2021. This study uses a quantitative descriptive method to determine the effect of the variables studied. And technical analysis with the Multiple linear regression analysis was used to test the hypothesis in this study. Based on data collected through documentation of reports on the realization of regency/city budgets in Aceh, it was found that: 1) Regional autonomy has no effect on financial performance; 2) The effectiveness of regional income has no effect on financial performance; 3) Regional expenditure has an effect and is significant on financial performance; and 4) Simultaneously the factors of regional autonomy, effectiveness of regional income, and regional expenditure affect financial performance with a contribution of 94,4 and the influence of other factors not involved in the analysis of financial performance is 5,6%.